Analisisis Efisiensi Modal Kerja, Likuiditas, Solvabilitas Terhadap Profitabilitas Perusahaan Kosmetik Bursa Efek Indonesia - Endang Purwanti; Safira Nurlita Ririantini; Ana Fitri Indrawati (Owner : Riset dan Jurnal Akuntansi, 2022)
The cosmetics industry sector has experienced significant growth. The increase in the growth of the cosmetics industry needs to be balanced with efficient working capital management, liquidity, solvency which will affect profitability. The purpose of this study is to determine working capital efficiency, liquidity, solvency affect the profitability of cosmetic companies on the Indonesia Stock Exchange for the period 2013-2020. Method of analysis Multiple Linear Regression analysis is used to determine the effect of working capital efficiency, liquidity, solvency on profitability in the Indonesian Stock Exchange cosmetics industry in 2013-2020, t test hypothesis test (partial), F test (simultaneous). The results of this study are regression test. multiple linear and partial hypothesis test there is a significant negative effect of working capital efficiency on profitability. If working capital efficiency increases, profitability will decrease, due to a decrease in sales due to the impact of the COVID-19 pandemic pressure in 2019 and 2020, but the company is still able to earn profits from investment returns. Liquidity has a positive and insignificant effect on profitability, high liquidity can lead to idle funds, unable to provide company profits. While solvency has no significant positive effect on profitability. Changes in solvency do not affect changes in profitability.